DOC and CO2-C Releases from Pristine and Drained Peat Soils in Response to Water Table Fluctuations: A Mesocosm Experiment - Merjo P. P. Laine; Rauni Strömmer; Lauri Arvola (Applied and Environmental Soil Science)
Hydrological conditions are considered to be among the main drivers influencing the export of dissolved organic carbon (DOC) from terrestrial to aquatic ecosystems, and hydrology is likely to alter due to climate change. We built a mesocosm experiment by using peat profiles from a pristine and from a drained (drained in 1978) peatland. A several-week-long low water table period followed by a high water table period, that is, a setting mimicking drought followed by flood, released relatively more DOC from pristine peat than from drained peat. From pristine peat profiles DOC was released into soil water in such quantities that the concentration of DOC remained stable despite dilution caused by added spring water to the mesocosms. In drained peat the DOC concentrations decreased during the high water table period indicating stronger dilution effect in comparison to pristine peat. At the landscape level DOC load from a drained peatland to the recipient water body may, however, increase during flooding because of high water runoff out of the peatland containing high DOC concentrations relative to the forest and agricultural areas. During the high water table period neither peat type nor water table had any clear impact on carbon dioxide (CO2-C) fluxes.